Теоретичні аспекти дослідження структурних трансформацій ринку праці - Ільїч, Л.М. (Управління економікою: теорія та практика, 2013)
Розглянуто теоретичні аспекти аналізу динаміки ринку праці. Сформульовано авторські визначення понять “ринок праці”, “структурна перебудова”, “структурна криза” та “структурна трансформація” ринку праці. Досліджено етапи та виділено рівні структурних трансформацій ринку праці. Класифіковано детермінанти структурних трансформацій ринку праці. Рассмотрены теоретическим аспекты анализа динамики рынка труда. Сформулированы авторские определения понятий«рынок труда», «структурная перестройка», «структурный кризис» и «структурная трансформация» рынка труда. Исследованы этапы и выделены уровни структурных трансформаций рынка труда. Классифицированы детерминанты структурных трансформаций рынка труда. The paper deals with theoretical aspects of the labor market dynamics. Structural reorganization of the labor market covers the process of gradual, progressive, coherent institutional and structural changes that lead to the formation of a qualitatively new mechanism of the labor market, which aims at ensuring the progressive development of the economic system. Structural crisis of the labor market is caused by controversy between the outdated elements of its structure and new elements that appear in response to the growing needs of the economy. Structural crisis of the labor market can be manifested in increased imbalance between supply and demand on the labor market, unemployment and forced underemployment, increasing the volume of informal employment, stagnation of introducing new jobs, etc. The structural transformation of the labor market is a process which encompasses all socio-economic conditions of the labor market functioning and is characterized by constant transition from a stable to unstable state (and vice versa) with subsequent transformation of its structural elements and relationships. Evolutionary structural transformation of the labor market involves the process of quantitative and qualitative changes in the elements of its structure. Revolutionary structural transformation of the labor market is subject to gradual accumulation of previous evolutionary shifts, which cause the fundamental change in all components of the labor market and its transition to a new qualitative level which corresponds to new conditions of social and economic development. The structural transformations of the labor market at different levels are interrelated and tend to accumulate themselves. Permanent single structural transformations of the labor market at the micro level are determined by completeness or incompleteness of the labor reproduction processes and may lead to transformations of reproduction processes of the labor market at higher levels (meso-, macro-, and mega-levels). Regulation of the structural transformation of the labor market should be implemented at every level, starting from change of motivation to the work of an individual subject until complete restructure of reproduction labor processes and improvement of the system of labor relations are achieved.